Invaders Exposed: Understanding and Targeting Tumor Cell Invasion in Diffuse Intrinsic Pontine Glioma - Kluiver, T. A.; Alieva, M.; van Vuurden, D. G.; Wehrens, Ellen J.; Rios, Anne C. (Frontiers in Oncology, 2020)
Diffuse Intrinsic Pontine Glioma (DIPG) is a rare, highly aggressive pediatric brain tumor that originates in the pons. DIPG is untreatable and universally fatal, with a median life expectancy of less than a year. Resection is not an option, due to the anatomical location of the tumor, radiotherapy has limited effect and no chemotherapeutic or targeted treatment approach has proven to be successful. This poor prognosis is partly attributed to the tumor’s highly infiltrative diffuse and invasive spread. Thus, targeting the invasive behavior of DIPG has the potential to be of therapeutic value. In order to target DIPG invasion successfully, detailed mechanistic knowledge on the underlying drivers is required. Here, we review both DIPG tumor cell’s intrinsic molecular processes and extrinsic environmental factors contributing to DIPG invasion. Importantly, DIPG represents a heterogenous disease and through advances in whole-genome sequencing, different subtypes of disease based on underlying driver mutations are now being recognized. Recent evidence also demonstrates intra-tumor heterogeneity in terms of invasiveness and implies that highly infiltrative tumor subclones can enhance the migratory behavior of neighboring cells. This might partially be mediated by ‘tumor microtubes’, long membranous extensions through which tumor cells connect and communicate, as well as through the secretion of extracellular vesicles. Some of the described processes involved in invasion are already being targeted in clinical trials. However, more research into the mechanisms of DIPG invasion is urgently needed and might result in the development of an effective therapy for children suffering from this devastating disease. We discuss the implications of newly discovered invasive mechanisms for therapeutic targeting and the challenges therapy development face in light of disease in the developing brain.